Petunjuk Dan Landasan Dalam Penetapan Garis Nasab Perspektif Hukum Islam - Ahmad Muhammad Sa'dul Kholqi (MASADIR: Jurnal Hukum Islam, 2023)
In Islamic jurisprudence, Nasab holds a crucial position, being one of the five elements categorized under "kulliyatul khoms" that demand safeguarding, thus subjecting it to the application of Islamic laws. The preservation of Nasab stands as a primary objective in the implementation of Islamic law, and its significance has escalated in the contemporary era. The prevalence of various deviations in the process of childbirth underscores the urgency of upholding this aspect. Furthermore, the Republic of Indonesia's legal framework recognizes numerous rights for children, emphasizing the necessity of a legitimate lineage for the entitlement to these rights. As Muslims residing in a nation governed by laws and regulations, it becomes imperative for us to comprehend the foundational aspects that contribute to the determination of our lineage. An awareness of these factors becomes pivotal, as it directly impacts our ability to establish lineage connections and, consequently, secure the associated legal rights within the societal and legal framework of Indonesia.